A Bioactive Polysaccharide Isolated from the Fruits of Chinese Jujube - Zhao, Zhi-Hui; Liu, Meng-Jun; Tu, Peng-Fei (Asian Journal of Chemistry, 2011)
A polysaccharide JuBP-4 with mean molecular mass of 1600KDa, was isolated from fruits of Ziziphus jujuba Mill. by fractionation on DEAE column and gel column chromatographies. Chemical and spectroscopic studies indicated that it is composed of rhamnose, arabinose, glucose, galactose and galacturonic acid in a molar ratio of 1:8.83:2.08:7.44:33.79. The main backbone chain in JuBP-4 is mostly composed with 1,4-linked a-D-galacturonic acid interspersed with 1,2-linked a-L-rhamnose and the side chains was mainly 1,5-linked a-arabinose residues and 1,6-linked b-galactose. The polysaccharide was demonstrated mitogenic activity properties.